2002
DOI: 10.1063/1.1518026
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study of intramultiplet transitions in collisions of C(3P) and Si(3P) with He

Abstract: Articles you may be interested inAb initio study of the RbSr electronic structure: Potential energy curves, transition dipole moments, and permanent electric dipole moments J. Chem. Phys. 141, 234309 (2014); 10.1063/1.4903791Collision-induced nonadiabatic transitions in the second-tier ion-pair states of iodine molecule: Experimental and theoretical study of the I 2 ( f 0 g + ) collisions with rare gas atoms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Usually they are included up to a highest level (l 0 ) chosen on physical ground.References. -(1)Launay & Roueff (1977a), (2)Lavendy et al (1991);; LePicard et al (2002), (3) Roueff & LeBourlot (1990), (4)Schroder et al (1991), (5)Pequignot & Aldrovandi (1976), (…”
mentioning
confidence: 99%
“…Usually they are included up to a highest level (l 0 ) chosen on physical ground.References. -(1)Launay & Roueff (1977a), (2)Lavendy et al (1991);; LePicard et al (2002), (3) Roueff & LeBourlot (1990), (4)Schroder et al (1991), (5)Pequignot & Aldrovandi (1976), (…”
mentioning
confidence: 99%
“…A typical example is the spin-orbit (de-)excitation of ground-state atomic carbon, C( 3 P j ) → C( 3 P j ), in collisions with He or H 2 . 24,25 This process is highly relevant for interstellar cloud cooling and plays an important role in chemical modelling of the interstellar medium. 26,27 To date, several experimental and theoretical studies concerning the collision-induced spin-orbit transitions in C( 3 P j ) atoms have been published.…”
Section: Graphical Toc Entrymentioning
confidence: 99%
“…26,27 To date, several experimental and theoretical studies concerning the collision-induced spin-orbit transitions in C( 3 P j ) atoms have been published. 24,25,[28][29][30][31][32] In particular, Bergeat et al reported experimental and theoretical integral cross sections (ICSs) for C( 3 P 0 ) + He → C( 3 P 1 / 3 P 2 ) + He collisions. 24 The excellent agreement between experiment and theory allowed a detailed description of resonance features in the collision energy dependent ICSs.…”
Section: Graphical Toc Entrymentioning
confidence: 99%
“…Bennett et al (2003) studied the role of quasi-bound states in the formation of LiH. Atom collisions can also result in changes in internal energy and recent work includes: Li with H (Belyaev & , He * with He (Vrinceanu & Sadeghpour 2002), and C and S with He (Le Picard et al 2002).…”
Section: Ion-atom and Atom-atom Collisionsmentioning
confidence: 99%